Economia solidária e a produção de peças transformáveis: uma proposta de inclusão social - Vereta, Magda Caroline (2015)
The present work consists in analyzing the effects on the governing body by the current system - capitalism. However, a new production method is presented, known as solidarity economy, whose purpose is the social inclusion of those who are considered economically unnecessary. The goal is to create a cooperative that serves the principles and guidelines of the solidarity economy for the production of convertible items of clothing, securing their viability for a possible implementation in the city of Apucarana - Paraná. However, in addition to social and economic inclusion of people in the labor market for the production of fashion products, they will be qualified according to the characteristics and market demand, observing the impacts that will be generated in the selected city.